Posttranscriptional Regulation of HO Expression by the Mkt1-Pbp1 Complex - Tadauchi, Tomofumi (American Society for Microbiology, 2004)
Cells of budding yeast give rise to mother and daughter cells, which differ in that only mother cells express the HO endonuclease gene and are thereby able to switch mating types. In this study, we identified the MKT1 gene as a positive regulator of HO expression. The MKT1 gene encodes a protein with two domains, XPG-N and XPG-I, which are conserved among a family of nucleases, including human XPG endonuclease. Loss of MKT1 had little effect on HO mRNA levels but resulted in decreased protein levels. This decrease was dependent on the 3′ untranslated region of the HO transcript. We screened for proteins that associate with Mkt1 and isolated Pbp1, a protein that is known to associate with Pab1, a poly(A)-binding protein. Loss of PBP1 resembles an mkt1Δ deletion, causing decreased expression of HO at the posttranscriptional level. Mkt1 and Pbp1 cosedimented with polysomes in sucrose gradients, with Mkt1 distribution in the polysomes dependent on Pbp1, but not vice versa. These observations suggest that a complex of Mkt1 and Pbp1 regulates the translation of HO mRNA.